Policing, politics, and democracy: David Bayley's enduring contributions. Issue 3 (3rd July 2021) - Cordner, Gary; Maguire, Edward R.; Shearing, Clifford
ABSTRACT: This special issue pays tribute to the life and work of David Hume Bayley, professor emeritus in the School of Criminal Justice at the University at Albany, who passed away in May of 2020 at the age of 87. We regard Bayley as the world's pre-eminent comparative policing scholar. In this introduction to the special issue, we begin by providing a brief synopsis of his evolution as a scholar, from his Ph.D. training in political science to his most recent work on the role of policing in democracy. We then introduce the articles that appear in this special issue and highlight how they derive from or intersect with Bayley's scholarship.